1990
DOI: 10.1111/j.1745-459x.1990.tb00492.x
|View full text |Cite
|
Sign up to set email alerts
|

Consistency of Multidimensional Scaling Models Derived From Odor Sorting

Abstract: ABSTRACT. The odor perceptions of six groups of subjects who varied in their degree of experience and training in odor evaluation were examined using a sorting task. Data were submitted to multidimensional scaling to produce perceptual models. Regardless of training or expertise, models of different subject groups were highly similar as measured by interpoint distance correlations (median r = 0.74). The retest correlation of one group tested twice with no intervening training was 0.85. A two‐dimensional model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
47
1
1

Year Published

1999
1999
2023
2023

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(55 citation statements)
references
References 18 publications
(16 reference statements)
6
47
1
1
Order By: Relevance
“…Panellists were asked to sort samples into as many groups as they wanted, based on their odour similarity. This non-verbal method has been used in several studies (Lawless & Glatter, 1990;Solomon, 1997) to assess similarities. Samples were presented according to a Latin square.…”
Section: Methodsmentioning
confidence: 99%
“…Panellists were asked to sort samples into as many groups as they wanted, based on their odour similarity. This non-verbal method has been used in several studies (Lawless & Glatter, 1990;Solomon, 1997) to assess similarities. Samples were presented according to a Latin square.…”
Section: Methodsmentioning
confidence: 99%
“…Several authors showed that the dimensions of multidimensional scaling (MDS) configurations resulting from an evaluation made by untrained panelists can be interpreted using the vocabulary generated (Chollet & Valentin, 2000;Hollins et al, 1993;Lim & Lawless, 2005;Lawless, 1989;Lawless et al, 1995). Lawless and Glatter (1990) showed that perceptive maps of odors obtained with trained or untrained panelists were relatively similar. Besides Chollet and Valentin (2001) demonstrated that vocabulary used by untrained panelists was not as accurate as that of trained panelists.…”
Section: Introductionmentioning
confidence: 98%
“…Even for a relatively large set of products, this sorting can be performed during a unique session: e.g. 13 liquids flavoured with vanilla (Heymann, 1994), 18 odors (Lawless & Glatter, 1990), 17 odors (Macrae, Rawcliffe, Howgate, & Geelhoed, 1992), 13 waters (Falahee & Macrae, 1995). In practice, these data are analysed after an aggregation into a matrix whose general term (row i, column l) is the number of subjects having sorted the products i and l in the same group.…”
Section: Introductionmentioning
confidence: 99%